2006
DOI: 10.1074/jbc.m507851200
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Apoptosis in the Protein Kinase Cδ Null Mouse in Vivo

Abstract: Protein kinase C (PKC)␦

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
158
4

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(178 citation statements)
references
References 51 publications
16
158
4
Order By: Relevance
“…The JNK pathway played a major role in the apoptotic effect of PKCyNuc because inhibition of JNK significantly decreased the apoptotic effect of the PKCy-Nuc. JNK has been implicated in the regulation of cell apoptosis in response to various stimuli (51,52) and has been shown to act downstream of PKCy (16,51,53,54). A role for the nuclear PKCy in the activation of JNK is further supported by recent studies that showed that the nuclear translocation of PKCy by etoposide preceded the activation of JNK in salivary gland acinar cells (30,53).…”
Section: Discussionsupporting
confidence: 48%
“…The JNK pathway played a major role in the apoptotic effect of PKCyNuc because inhibition of JNK significantly decreased the apoptotic effect of the PKCy-Nuc. JNK has been implicated in the regulation of cell apoptosis in response to various stimuli (51,52) and has been shown to act downstream of PKCy (16,51,53,54). A role for the nuclear PKCy in the activation of JNK is further supported by recent studies that showed that the nuclear translocation of PKCy by etoposide preceded the activation of JNK in salivary gland acinar cells (30,53).…”
Section: Discussionsupporting
confidence: 48%
“…Furthermore, PKC plays a pivotal role in the genotoxic stress response leading to apoptosis in various cell types (Brodie and Blumberg 2003, Reyland 2007, Yoshida 2007a). In addition, cells derived from PKC -/-mice were shown to be defective in mitochondria-dependent apoptosis (Humphries et al 2006, Leitges et al 2001. These findings thus support our proposition of a pro-genotoxic role for PKC.…”
Section: Pkc and Apoptotic Cell Death Upon Genotoxic Insultssupporting
confidence: 79%
“…For example, PKC activators enhanced caspase activation, whereas an inhibitor of PKC prevented caspase activation in response to DNA damage (Basu et al 2001). In particular, studies with PKC -/-mice suggest that PKC plays pivotal roles in the regulation of cell proliferation and apoptosis (Humphries et al 2006, Leitges et al 2001. PKC is activated by a variety of stimuli including ionizing radiation, anti-cancer agents, reactive oxygen species (ROS), ultraviolet radiation, growth factors and cytokines (Carpenter et al 2002, Chen et al 1999, Denning et al 1996, Konishi et al 2001, Reyland et al 1999, Yoshida and Kufe 2001.…”
Section: Pkc and Apoptotic Cell Death Upon Genotoxic Insultsmentioning
confidence: 99%
“…Protein kinase Cd may be activated in response to Ara-C as demonstrated in U937 human leukaemia cells (Emoto et al, 1996), cisplatin in H69 human small-cell lung cancer cells (Persaud et al, 2005), and etoposide in human glioma cells (Blass et al, 2002). Interestingly, apoptosis was severely impaired when the PKCd function or expression was inhibited (Humphries et al, 2006). In addition, activation of PKCd may cause G1 and G2 cell cycle arrest through the modulation of cyclin and cyclin-dependent kinase expression (Griner and Kazanietz, 2007).…”
mentioning
confidence: 99%